Historical Impact of Messianic Prophecies on Ancient And Modern Times - Laoly, Nepho Gerson (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Abstract: This article delves into the significance of messianic prophecies in Judaism and Christianity, examining their origins, impact on ancient Israel, and relevance in modern times. The study uses literary analysis and hermeneutic approaches to examine the history, interpretation, and contextualization of these prophecies. It discusses their influence on ancient Israel's religious and cultural identity, fostering optimism during turmoil. The article also explores their impact on various global regions.. The article also emphasizes the significance of messianic prophecies in contemporary society, shaping religious beliefs, fostering collective belief systems, and influencing social and political dynamics. The article highlights the ongoing scholarly discourse and theological deliberation surrounding these prophecies, revealing their persistent importance in today's theological and cultural frameworks. Overall, this comprehensive examination of messianic prophecies provides a deeper understanding of religious convictions, cultural customs, and the evolution of religious movements. Christian can affirm that Jesus is God and Lord who protect His people. Keywords: Messianic ; Ancient Israel ; Judaism ; Sociological Context ; Christianity  Abstrak: Artikel ini menyelidiki pentingnya nubuat-nubuat Mesias dalam Yudaisme dan Kekristenan, memeriksa asal-usul mereka, dampaknya pada Israel kuno, dan relevansi mereka di zaman modern. Studi ini menggunakan analisis sastra dan pendekatan hermeneutik untuk memeriksa sejarah, interpretasi, dan kontekstualisasi dari nubuat-nubuat ini. Ini membahas pengaruh mereka pada identitas agama dan budaya Israel kuno, mendorong optimisme selama kekacauan. Artikel ini juga mengeksplorasi dampaknya pada berbagai wilayah global. Artikel ini juga menekankan pentingnya nubuat messianik dalam masyarakat kontemporer, membentuk keyakinan agama, mempromosikan sistem kepercayaan kolektif, dan mempengaruhi dinamika sosial dan politik. Artikel ini menyoroti diskusi ilmiah yang sedang berlangsung dan pertimbangan teologis yang mengelilingi nubuat-nubuat ini, mengungkapkan pentingnya yang berterusan dalam kerangka teologi dan budaya saat ini. Secara keseluruhan, pemeriksaan yang komprehensif terhadap nubuat-nubuat messian memberikan pemahaman yang lebih mendalam tentang keyakinan agama, kebiasaan budaya, dan evolusi gerakan agama. Orang Kristen dapat menyatakan bahwa Yesus adalah Tuhan dan Tuhan yang melindungi umat-Nya. Kata Kunci : Mesias; Israel Kuno; Yudaisme; Konsteks Sosialogi; Kekristenan